The Influence of Store Atmosphere and Visual Merchandising on Impulse Buying at Uniqlo Store Duta Mall Banjarmasin - Humaidi Humaidi; Syamsur Rahman (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The purpose of this study is to test the partial and simultaneous influence of Store Atmosphere and Visual Merchandising variables on Impulse Buying at Uniqlo Store Duta Mall Banjarmasin. The method used is quantitative using a survey method research design with an explanatory research type. A sample of 100 respondents using the Incidental Sampling technique. Data analysis using multiple linear regression assisted by IBM SPSS Statistics Version 25. The results of this study prove that Store Atmosphere and Visual Merchandising have a significant partial and simultaneous influence on Impulse Buying at Uniqlo Store Duta Mall Banjarmasin. The dominant influence on Impulse Buying is store atmosphere. Keywords: Store Atmosphere, Visual Merchandising, Impulse Buying